Selective photoregulation of the activity of glycogen synthase and glycogen phosphorylase, two key enzymes in glycogen metabolism. Issue 26 (14th July 2015) - Díaz-Lobo, Mireia; Garcia-Amorós, Jaume; Fita, Ignacio; Velasco, Dolores; Guinovart, Joan J.; Ferrer, Joan C.
<x xml:space="preserve">Abstract</x> An azobenzene glucoside was synthesized and was shown to be an excellent selective inhibitor of Escherichia coli glycogen synthase in its photogenerated (Z)-form, which structurally resembles the three terminal glucoses of a glycogen branch.